2001
DOI: 10.1046/j.1355-557x.2001.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Weaning Chinese perchSiniperca chuatsi(Basilewsky) onto artificial diets based upon its specific sensory modality in feeding

Abstract: Chinese perch are one of the most valuable food ®sh in China, but the sole source of feed for intensive culture is live prey ®sh. Our previous studies on systematic sensory physiology revealed that this species have a mechanism for this peculiar feeding habit. In the present study, a speci®c training procedure was designed, and both experimental (initial body weight 171.0 g; 120 days) and commercial (initial body weight 52.4 g; 240 days) netcage cultures were conducted to investigate the training success, grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 18 publications
0
74
0
Order By: Relevance
“…Domestication of food habit was performed by following the methods of Liang et al (2001) using net-cages as the experimental culture in Guangdong Freshwater Fish Farm (Panyu, Guangdong, China). In this study, fry of Indian mrigal, Cirrhina mrigola, was used as the live prey fish for mandarin fish and the dead prey fish were prepared by freezing.…”
Section: Fish and Dna Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Domestication of food habit was performed by following the methods of Liang et al (2001) using net-cages as the experimental culture in Guangdong Freshwater Fish Farm (Panyu, Guangdong, China). In this study, fry of Indian mrigal, Cirrhina mrigola, was used as the live prey fish for mandarin fish and the dead prey fish were prepared by freezing.…”
Section: Fish and Dna Samplesmentioning
confidence: 99%
“…And due to the special feeding habit of mandarin fish, its aquaculture industry is still restricted. So, Liang et al (2001) designed a specific training procedure and found that most of the mandarin fish could feed minced prey fish successfully while some fish still refused. This suggested that food habit domestication traits of mandarin fish may vary among individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Siniperca chuatsi (Basilewsky) and Siniperca kneri (Garman) are two important perciform species with a wide distribution from the southern Zhujiang River system to the north in the Huaihe River system in China (Han et al, 1996;Liang et al, 2001). They are two of the most valuable food fish and two important piscivorous species, having specialized feeding habits of only feeding on live fish or shrimp throughout their life (Liang et al, 1998;Li et al, 2005Li et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Mandarin fish, or Chinese perch, Siniperca chuatsi (Basilewsky), is an important commercial freshwater fish inhabiting in the waters from the south in the Zhujiang River system to the north in the Amur River system (Liang et al 2001). Mandarin fish is a piscivore throughout its life and is adapted to the nocturnal stalking hunting strategy (Liang et al 1998(Liang et al , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Mandarin fish is a piscivore throughout its life and is adapted to the nocturnal stalking hunting strategy (Liang et al 1998(Liang et al , 2001). In the past several decades, the resources of mandarin fish in the Yangtze lakes have declined dramatically due to overfishing and eutrophication.…”
Section: Introductionmentioning
confidence: 99%